2017
DOI: 10.4314/ovj.v7i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intraocular pressure and horizontal pupil diameter during use of topical mydriatics in the canine eye

Abstract: The objective of this study was to determine the effects of topical 0.5% tropicamide, 1% atropine sulphate and 10% phenylephrine hydrochloride ophthalmic solutions on intraocular pressure (IOP) and horizontal pupil diameter (HPD) in the dog during the first hour after treatment. Forty clinically and ophthalmologically normal canine patients (between the ages of 2 and 6 years) of varying breed and sex were used in this study. Animals were randomly divided into four groups of ten and given one drop of tropicamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…In Latvian Hunting dogs, we calculated the normal range of IOP as 11.3-24.1 mmHg (mean±SD of 17.7±3.2 mmHg in both eyes). These values are slightly higher than in a previous study of mixed dog breeds, where IOP ranged from 12.8±1.8 mmHg to 17.7±3.1 mmHg [30] and similar to other author reported values -from 16.7±4.0 mmHg to 18.7±5.5 mmHg [7,31].…”
Section: Discussionsupporting
confidence: 87%
“…In Latvian Hunting dogs, we calculated the normal range of IOP as 11.3-24.1 mmHg (mean±SD of 17.7±3.2 mmHg in both eyes). These values are slightly higher than in a previous study of mixed dog breeds, where IOP ranged from 12.8±1.8 mmHg to 17.7±3.1 mmHg [30] and similar to other author reported values -from 16.7±4.0 mmHg to 18.7±5.5 mmHg [7,31].…”
Section: Discussionsupporting
confidence: 87%
“…In addition to sample size, another potential limitation of the study is the use of tropicamide and proparacaine prior to the measurement of IOP, which may have influenced the IOP readings 1 . One recent study showed that tropicamide increased IOP in dogs by 8.8 ± 4.0 mmHg by 35 minutes post‐treatment compared to pre‐treatment, 31 while another study showed that the majority (60%) of dogs displayed 5 mmHg or less in IOP change post‐mydriasis 32 . Topical anesthetics, on the other hand, tend to reduce IOP readings 27,33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Structures posterior to the iris were successfully evaluated with the use of tropicamide 1% eye drops once the pupil was 50%‐60% dilated. Tropicamide‐induced mydriatic induction occurred faster in sugar gliders (7.2 ± 2.7 minutes with a range of 5 to 14 minutes) than in dogs (20 minutes), 12 or another marsupial, the red kangaroo (mean of 16.7 ± 3.34 minutes) 13 . The rapidity of dilation in sugar gliders is convenient for minimizing anesthetic time associated with ophthalmic examination.…”
Section: Discussionmentioning
confidence: 97%